Lethal and sublethal effects of eucalyptol on vectors of Chagas disease Triatoma infestans and Rhodnius prolixus (Hemiptera: Reduviidae) - Moretti, Ariadna Noelia (2015)
Eucalyptol is the common name for a cyclic ether monoterpene found in essential oils from Eucalyptus species and other plants. Several reports showed its insecticidal activity. In this work, visible symptoms of intoxication, effect on locomotor activity, knock-down, and repellence produced by eucalyptol were evaluated on nymphs of Triatoma infestans Klug and Rhodnius prolixus Stahl (both Hemiptera: Reduviidae). Both insects are among the main vectors of Chagas disease in Latin America. Visible symptoms of intoxication were similar to those observed for neurotoxic insecticides. A video tracking technique was used to evaluate locomotor activity and repellence by exposing thE nymphs to impregnated papers. Hyperactivity (a non-directional increase in locomotor activity) is a symptom of intoxication that is used to detect triatomines in rural houses, because it causes the insects to leave their refuges. Eucalyptol produced hyperactivity only in T. infestans at a concentration 1 000x higher than the positive control, deltamethrin [(S)-cyano(3-phenoxyphenyl)methyl (1R,3R)-3-(2,2-dibromoethenyl)-2,2-dimethylcyclopropanecarboxylate]. It also produced repellence on both species at a concentration 10x higher than the positive control, DEET (N,N-diethyl-3-methylbenzamide). Knock-down effect was evaluated by exposing the nymphs to impregnated papers in closed containers (contact and fumigation simultaneously). Values of knock-down time for 50% of exposed nymphs (KT50) were calculated for various concentrations of eucalyptol. The onset of knock-down occurred more rapidly as the concentration increased. In the best cases, eucalyptol was 12-15x less toxic than the positive control dichlorvos (2,2-dichlorovinyl dimethyl phosphate). After these results, eucalyptol seems discouraged as a hyperactivant agent for monitoring insects in rural houses. Nevertheless, its knock-down and repellence effect on vectors of Chagas disease deserve further investigation.